The ongoing effects and impact of hearing loss and tinnitus associated with platinum based chemotherapy in adults living with and beyond cancer - Pearson, Stephanie (2022)
Many adults living with and beyond cancer (LWBC) are impacted by the multitude of toxicities associated with chemotherapy treatment. For example, platinum based chemotherapy (PBC) is known to cause ototoxicity, presenting as hearing loss and tinnitus. There is a paucity of good-quality information and support offered to patients who experience ototoxicity, which can subsequently lead to many being undiagnosed and untreated.